International financial reporting standards : a practical guide - Greuning, Hennie van. (Washington, D.C. : World Bank, 2010)
The book gives private or public sector executives, managers, and financial analysts, who may not have a strong background in accounting, the tools they need to participate in discussions and decisions on the appropriateness or application of IFRS.
ucj 11/09/18
Loans
Keywords: Accounting; Financial statements